Atomistic origins of the differences in anisotropic fracture behaviour of LiTaO3 and LiNbO3 single crystals. (15th May 2018) - Gruber, M.; Konetschnik, R.; Popov, M.; Spitaler, J.; Supancic, P.; Kiener, D.; Bermejo, R.
Abstract: The search of new designs for communication technologies is driven by the required high data transfer rates. Piezoelectric single crystals such as LiTaO3 and LiNbO3 have qualified as materials for efficient and precise frequency filters also considered for the new 5G standards. To ensure optimal high frequency functionality, single crystal wafers are grown and cut in particular directions. However, due to the high anisotropic physical properties of these brittle materials, the structural integrity and reliability of devices are affected by the crystal orientation with respect to the occurring thermo-mechanical stresses. In this work, the anisotropic fracture response of LiTaO3 and LiNbO3 single crystals is investigated through combination of (i) toughness measurements in notched micro-cantilevers along weak cleavage planes and (ii) atomistic modelling of cleavage fracture energies using density functional theory. It is demonstrated that differences in fracture behaviour between LiTaO3 and LiNbO3 can be explained by the stronger chemical bonding in LiTaO3 as compared to LiNbO3 within the loaded crystallographic planes. The knowledge on the alignment of tough as well as weak planes (i.e. cleavage planes) can be used to tailor the design of single crystal based functional components, aiming to exhibit enhanced mechanical reliability without compromising the functionality. Graphical abstract: Image 1